1995
DOI: 10.1128/jcm.33.9.2366-2371.1995
|View full text |Cite
|
Sign up to set email alerts
|

Use of random amplified polymorphic DNA as a typing method for Candida albicans in epidemiological surveillance of a burn unit

Abstract: Burn patients are particularly exposed to deep-seated nosocomial infections caused by Candida species. Superficial carriage of C. albicans is a potential source of infection and dissemination, and typing methods could be useful to trace the different isolates. We report the use of random amplified polymorphic DNA to type isolates of C. albicans in the Hôpital Cochin burn unit. This molecular typing method, which is based on PCR with arbitrary short primers, was evaluated on a panel of 32 C. albicans strains is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…[12][13][14][15][16][17] Many authors have reported that RAPD-PCR could be used to type Candida species with high discriminative power, 20,29 as high as 0.97 in one study in which 84 C. albicans strains isolated from burn unit patients were examined. 30 Becker et al, 21 in their study dealing with C. glabrata, concluded that RAPD-PCR was simple, inexpensive and could be applied to many strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14][15][16][17] Many authors have reported that RAPD-PCR could be used to type Candida species with high discriminative power, 20,29 as high as 0.97 in one study in which 84 C. albicans strains isolated from burn unit patients were examined. 30 Becker et al, 21 in their study dealing with C. glabrata, concluded that RAPD-PCR was simple, inexpensive and could be applied to many strains.…”
Section: Discussionmentioning
confidence: 99%
“…Band patterns of two isolates can be transformed into numerical values such as similarity coefficients. Dice coefficient was the most frequently used one for Candida species in studies reporting similarity coefficients, 11,22,23,30,31 thus we used this coefficient as well. Soll 12 reminds us that no standard evaluation criteria have been validated for the RAPD-PCR test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Random amplification of DNA Random amplification of DNA (RAPD), described by Williams et al [22], is one of the most applied techniques for the survey of the epidemiology of Candida glabrata and other fungi. 23,24 Using random primers of approximately 10 bases, amplicons throughout the genome are targeted and amplified. Amplified products are separated on agarose gel and stained with ethidium bromide.…”
Section: Restriction Enzymatic Electrophoresismentioning
confidence: 99%